2012
DOI: 10.1063/1.4772267
|View full text |Cite
|
Sign up to set email alerts
|

Unidentified VHE γ-ray sources and evolved pulsar wind nebulae - A possible connection?

Abstract: Abstract. Among Galactic VHE (very high energy, E > 100 GeV) γ-ray sources, pulsar wind nebulae (PWNe) form the most abundant class. At the same time, there are numerous sources of VHE γ-rays which are still unidentified. A firm identification of such objects requires a counterpart at other wavelengths. Middle-aged PWNe may account for many of these unidentified sources. While leptons that have been injected into a PWN a long time ago can still cause the observed VHE γ-ray flux, the present energy output of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 8 publications
1
6
2
Order By: Relevance
“…This magnetic field evolution is similar to the t −1.3 − t −2 behavior derived by Reynolds & Chevalier (1984) and the t −1.7 evolution of Gelfand et al (2009) during the initial expansion phase. The power-law evolution of the magnetic field is similar to that adopted by Zhang et al (2008), Lemiere et al (2009), Mayer et al (2012 for similarly aged PWNe.…”
Section: Discussionsupporting
confidence: 53%
“…This magnetic field evolution is similar to the t −1.3 − t −2 behavior derived by Reynolds & Chevalier (1984) and the t −1.7 evolution of Gelfand et al (2009) during the initial expansion phase. The power-law evolution of the magnetic field is similar to that adopted by Zhang et al (2008), Lemiere et al (2009), Mayer et al (2012 for similarly aged PWNe.…”
Section: Discussionsupporting
confidence: 53%
“…This means that the linear function improves the fit at only the 1σ level. This coefficient and this comparison show that, contrary to the expectation (Mayer et al 2012), no downward correlation is observed. However, this correlation might be obscured by the usage of the characteristic age of the pulsar, which may not be a good age estimator for the PWN.…”
contrasting
confidence: 65%
“…These figures show that the Fermi-LAT mainly detects young and middle-aged PWNe (1-30 kyr) around energetic pulsars with spin-down powers between 10 36 and 10 39 erg s −1 . One can see from these figures that the VHE sources older than 30 kyr are not detected by the LAT, while Mayer et al (2012) predict a higher flux in the LAT energy range than in the VHE experiments' energy range. However, it should be noted that among these nine VHE sources, at least seven suffer one or several biases.…”
Section: Table 11mentioning
confidence: 87%
See 1 more Smart Citation
“…An estimate of the contribution to the measured diffuse emission from sources with lower fluxes would require a model of a full synthetic population of PWNe based on H.E.S.S. and Fermi data and on the current theories of PWN evolution (e.g., Bucciantini et al 2011;Mayer et al 2012;Torres et al 2014). This study is beyond the scope of the present paper.…”
Section: Treatment Of the Unresolved Sourcesmentioning
confidence: 99%